Curcumin induce DNA damage and apoptosis through generation of reactive oxygen species and reducing mitochondrial membrane potential in melanoma cancer cells - Kocyigit, Abdurrahim; Guler, Eray Metin (Cellular and Molecular Biology, 2017)
Melanoma is the most malignant skin cancer. Curcumin has shown to have therapeutic effects when used in the treatment of malignant diseases. However, the precise molecular mechanisms of its action are not fully elucidated. In this research, we hypothesized that reactive oxygen species (ROS) play a key role in curcumin induced DNA damage, apoptosis and cell dead. To test our hypothesis, cytotoxic, genotoxic, apoptotic, ROS generating and mitochondrial membrane potential (MMP) of curcumin on mouse melanoma cancer cells (B16-F10) and fibroblastic normal cells (L-929) were investigated. Our results demonstrated that curcumin decreased cell viability and MMP and, increased DNA damage, apoptosis and ROS levels in both melanoma cancer and normal cells in a dose dependent manner and, these activities were significantly higher in melanoma cells than in normal cells with higher concentrations. There were positive strong relationships between DNA damage, apoptosis, cytotoxicity and ROS generation and MMP levels in curcumin treated melanoma and normal cells. In summary, this in vitro study provide clear evidence that curcumin induced DNA damage, apoptosis and cytotoxicity via its pro-oxidant activity in a dose dependent manner in both cancer and normal cells and these activities were higher in cancer cells than those of normal cells.